Avifauna assemblage in Apo Island, Negros Oriental, Philippines outcomes of a community-based biodiversity monitoring approach - Detecio, Edmar R.; Oracion, Jean Henri M. (2024)
Apo Island belongs to the jurisdiction of the Municipality of Dauin, Negros Oriental, the Philippines, and it has been a part of long-term social and marine studies. However, information on the terrestrial ecosystem is lagging behind. The growing interest of the local community and organizations in terrestrial biodiversity led to the implementation of the biodiversity monitoring system (BMS). This was initiated by the protected area managers through the support of experts in the province. The enhanced BMS aims to equip the local community with knowledge on monitoring, as well as provide reliable baseline information for the protected area. With this effort, this paper provides baseline information initially on the birds of Apo Island, as they are valuable indicators of biodiversity. Birds are ecologically important species, and through their presence, it would be easy to evaluate for any changes in the ecosystem. Data was obtained through the line-transect and point-count method, and a 7-min observation was done at every 250-m point interval. Despite the relatively small land area, the survey specifically observed 27 species belonging to 21 families; nine of these are endemic to the Philippines, 16 are residents, and two are migrants. The island supports higher diversity and abundance, especially during the wet season. Furthermore, eight feeding guilds were also observed that can help shape the structure of other ecological communities. Most of the birds found in Apo Island are widespread in neighboring larger islands – indicative of an occurrence of local migration or colonization – and most of the birds recorded are of “least concern” conservation status. No island endemic is found. The different bird-feeding guilds observed imply various niches occupied that help shape the ecosystem. To better understand the distribution of the birds on the island, characterization of the habitat and quantifying its influence would be the best step forward.
Keywords: Birds; Biodiversity conservation; Habitat (Ecology) - Conservation; Apo Island (Dauin, Negros Oriental)